LATE CENOZOIC AND MODERN STRESS FIELDS IN THE WESTERN FARS (IRAN): IMPLICATIONS FOR THE TECTONIC AND KINEMATIC EVOLUTION OF CENTRAL ZAGROS - Lacombe O.; Mouthereau F.; Meyer B.; Kargar S. (My University, 2006)
The Zagros (Iran) developed during Mio-Pliocene times in response to Arabia-Eurasia convergence. The western Fars highlights a major bend of the deformation front and displays a remarkable set of nearly N-S right-lateral strike-slip faults (the Kazerun-Borazjan/Karebass/ Sabz-Pushan/Sarvestan faults) oblique at high angle to the belt. The region likely plays a major kinematic role by accommodating the change in shortening modes from partitioned in the western central Zagros to nonpartitioned in the eastern Zagros. The inversion of focal mechanisms from small and moderate earthquakes shows a consistent N020°-030° compression with a low ratio between differential stresses. This regime accounts for the combination of strike-slip and thrust-type mechanisms through likely σ2/σ3 permutations. Fault slip analysis reveals two successive late Cenozoic regional compressional trends, NE-SW then N020°. The latter is in good agreement with the present-day stress. The significance of the NE-SW compression is discussed alternatively in terms of stress deviations or block rotations in relation to the strike-slip fault system. Fieldwork and satellite imagery suggest that these faults behave first as transfer faults during folding of the cover and later as strike-slip faults, in agreement with the succession of stress regimes and the evolution of the dominant deformation style from thin-skinned to thick-skinned. The first-order stability of the collision-related state of stress since ~5 Ma supports that the Arabia-Eurasia convergence did not give rise to partitioning in the western Fars but rather was (and is still) accommodated by distributed deformation involving both shortening and strike-slip motion throughout the cover and the basement. Copyright 2006 by the American Geophysical Union.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен